Blood pressure measurement – an overview (Swiss Medical Weekly, 2012)
Arterial hypertension continues to represent the leading cause of morbidity and mortality world-wide. Diagnosis and therapy of arterial hypertension require adequate blood pressure measurements. Blood pressure is affected by constitutional and environmental factors as well as the measurement procedure itself, inducing substantial uncertainty with regard to adequate diagnosis and control of arterial hypertension. Therefore, current guidelines recommend that the diagnosis of arterial hypertension should not be solely based on conventional blood pressure measurements in the physician’s office or in the hospital, but also on out-of-office ambulatory or home blood pressure measurements using clinically validated semi-automated or automated blood pressure measurement devices. Despite the enormous progress in the field of arterial hypertension, many aspects of blood pressure measurement require further intensive investigation, for example blood pressure measurement in special populations and distinct clinical situations, as well as the applicability and validation of novel measurement approaches and devices. This article provides an overview of current methods and trends in the field of non-invasive blood pressure measurement, an update on current clinical guidelines and an overview of blood pressure measurement in special populations.